Effects of regular physical exercise on serum leptin and androgen concentrations in young women - Kumru, Selahattin; Ozmerdivenli, Recep; Aydin, Suleyman; Yasar, Abdullah; Kilic, Nermin; Parmaksiz, Cem; Aydin, Suna (My University, 2005)
Background: The effects of short-term and long-term regular exercise on body mass index and early follicular phase serum levels of leptin, testosterone and dehydroepiandrosterone sulfate in young female subjects are presented in this study. Methods: Volunteer young women (n = 94) participated. The volunteers were divided into three groups. Group I, the control group had a sedentary lifestyle. Group II had exercised regularly for more than 10 hours a week for 5 years. Group III had exercised for over 10 hours a week for more than 5 years. The serum leptin concentrations were determined using a specific human leptin radioimmunoassay. The testosterone and dehydroepiandrosterone sulfate concentrations were also determined radioimmunologically. Results: Compared with sedentary control subjects (group I), age-matched subjects with short-term (group II) and long-term (group III) sporting activity showed a statistically significant decrease in BMI (p < 0.05, group II; p < 0.001, group III) and serum leptin levels (p < 0.05, group II; p < 0.001, group III), as well as significantly higher testosterone levels (p < 0.05, both exercise groups). There were no significant differences for the levels of dehydroepiandrosterone sulfate between any of these groups (p > 0.05). Conclusions: In young women, regular physical exercise activities decrease the BMI and serum leptin levels and increase serum testosterone levels. Increased serum testosterone levels appear not to be a cause for hirsuteness or menstrual cycle abnormalities. The levels of dehydroepiandrosterone sulfate do not appear to be affected by exercise. © 2005 WPMH GmbH. Published by Elsevier Ireland Ltd.
Keywords: BMI; Dehydroepiandrosterone sulfate; Exercising female; Leptin; Testosterone